Pelatihan Pemanfaatan Limbah Plastik Menjadi Berbagai Kreasi Daur Ulang Bagi Masyarakat Desa Penyak - Yuant Tiandho; Herman Aldila; Yekti Widyaningrum; Tri Kusmita; Anisa Indriawati; Widodo Budi Kurniawan; Fitri Afriani (Universitas Islam Indonesia, 2021)
As an archipelago, handling plastic waste in the Province of Bangka Belitung Islands is an aspect that needs to be taken seriously. Apart from being focused on developing tourist areas, plastic waste will easily be carried to the sea and prone to be degraded into microplastics, often consumed by marine animals. This community service activity focuses on Penyak Village, Kec. Koba, Kab. Central Bangka, Bangka Belitung Islands. To solve the plastic problem in that location, the community service team conducted training for the community, especially for Pendidikan Kesejahteraan Keluarga (PKK) members, related to processing plastic waste into various recycled creations such as bags, pencil cases, and different kinds of souvenirs. The training program is carried out by providing materials and direct training to increase the understanding and skills. To broaden people's insights, the team conducted training with the Ecoplantstic start-up, which focuses on developing waste-based products. Through the evaluation, it is known that the training provided can improve the knowledge and skills of the community in processing plastic waste into various recycled creations, and several participants plan to develop the skills acquired for entrepreneurial purposes.